Investigation of simple portable telescope validity for muon detection inside metals - Rasha N.I. Altameemi,; Nurul Shazana Abdul Hamid,; Wan Mohd Aimran Wan Mohd Kamil,; Saad M. Saleh Ahmed,; Geri Gopir, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Muons produced in the atmosphere by cosmic rays are preferred over gamma rays, X-rays and fast protons for the detection of metals in the study of radiography. An alternative method for metals detection involving portable and relatively cheap Geiger-Muller counters are proposed. The objective of this study was to investigate the validity of using a handmade muon telescope with a small solid angle for the detection of muons inside the metals. This experiment was carried out at Universiti Kebangsaan Malaysia, Bangi (101.78º E, 2.92º N and elevation 30 m). Measurement of muons was conducted in the vertical direction using 1 set of muon telescopes (MT) consisting of coaxial Geiger-Muller (GM) counters. Different metals - lead (Pb), zinc (Zn) and aluminium (Al) - were used as absorbers with different thickness to observe its influence on the count rate of muons. The efficiency of the experimental setup was evaluated using statistical methods and by obtaining sufficient number of muon detection events to describe the physics of the muon interaction with the metals. Based on the Rossi curve obtained for each metal, the transition point was estimated as follows: 1.5 cm for Pb, 4.0 cm for Zn, and 9.0 cm for Al. The results showed that the proposed alternative setup was adequate for detecting muons and therefore have the potential to be further developed.